Diabetes mellitus aggravates myocardial inflammation and oxidative stress in aortic stenosis: a mechanistic link to HFpEF features - Herwig, Melissa; Sieme, Marcel; Kovács, Andrea; Khan, Muchtiar; Mügge, Andreas; Schmidt, Wolfgang E.; Elci, Ferhat; Sasidharan, Shan; Haldenwang, Peter; Wintrich, Jan; Sasko, Benjamin; Akın, Ibrahim; et al. (Cardiovascular diabetology, 2025)
Patients diagnosed with both aortic stenosis (AS) and diabetes mellitus (DM) encounter a distinctive set of challenges due to the interplay between these two conditions. This study aimed to investigate the effects of DM on the left ventricle in AS patients, specifically focusing on the inflammatory response, oxidative stress, and their implications for cardiomyocyte function, titin phosphorylation, and the nitric oxide (NO)-soluble guanylyl cyclase (sGC)-cyclic guanosine monophosphate (cGMP)-protein kinase G (PKG) signaling pathway.